2014
DOI: 10.5468/ogs.2014.57.6.464
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of green tea polyphenol against cisplatin-induced nephrotoxicity in rats

Abstract: ObjectiveThis study is to compare the effects of green tea polyphenol (GTP) pre-treatment with those of GTP post-treatment on cisplatin (CP)-induced nephrotoxicity in rat.MethodsMale Sprague-Dawley rats were randomly divided into six groups. Animals in the control group received 0.9% saline (intraperitoneal); animals in the GTP group received 0.9% saline and GTP (0.2% GTP as their sole source of drinking water); the CP group received only CP (7 mg/kg, intraperitoneal); the CP+preGTP group received GTP from two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
4
9
0
Order By: Relevance
“…These findings, suggestive of focal acute tubular necrosis, were compatible with the results of previous studies involving kidney damage induced with cisplatin (Ateşşahín et al, 2005(Ateşşahín et al, , 2007Ç ayır, 2011;Ahn et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings, suggestive of focal acute tubular necrosis, were compatible with the results of previous studies involving kidney damage induced with cisplatin (Ateşşahín et al, 2005(Ateşşahín et al, , 2007Ç ayır, 2011;Ahn et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Many fruit and vegetables are well-known for their powerful anti-oxidant activities. For that reason, various anti-oxidant agents have been investigated in red pepper (Shimeda et al, 2005), ginkgo biloba extract (Gulec et al, 2006), melatonin (Kilic et al, 2013), vitamin E (Kanter et al, 2007), vitamin C (Chen et al, 2014), lycopene (Atessahin et al, 2005, thymol (thyme oil) (Hosseinimehr et al, 2015), black tea (tannic acid) (Ahmed & Sultana, 2012), turmeric (curcumin, Indian saffron) (Sahin et al, 2014) and green tea (Ahn et al, 2014) for their protective effects against nephrotoxicity.…”
Section: Discussionmentioning
confidence: 98%
“…The compounds such as catechin, epigallocatechin and epigallocatechin gallate (EGCG) found in green tea have been reported to be effective against nephrotoxicity. 12 A study carried out on mice with cisplatin-treatment showed that pre-treatment with polyphenols (EGCG and epigallocatechin) led to decline the toxic changes, cisplatin-induced side effects and improved renal function in mice 13 thus, it was also found that administration of 20-40 mg/kg of catechin and EGCG led to decline in tumour necrosis factor alpha (TNF-α) and MDA (malondialdehyde) and enhanced glutathione level.…”
Section: Catechin Epigallocatechin and Epigallocatechin Gallatementioning
confidence: 99%
“…Catechin, epigallocatechin-gallate, and epigallocatechin: The compounds found in green tea such as catechin, epigallocatechin gallate (EGCG), and epigallocatechin have been reported to be effective in protection against nephrotoxicity ( 45 ). A study on cisplatin-treated mice demonstrated that pretreatment with green tea polyohenols (EGCG, and epigallocatechin) decreased toxic changes and cisplatin-induced side effects and improved renal function in the mice under treatment ( 46 ). In addition, El-Mowafy et al found that administration of 20-40 mg/kg of green tea catechin and EGCG led to decrease in tumor necrosis factor alpha (TNF-α) and MDA and increased glutathione level.…”
Section: Resultsmentioning
confidence: 99%